The Effect of Educational Competencies and Qualifications on the Performance of UPBU D.C. Saudale Office Employees with Organizational Commitment as an Intervening Variable - Rizwandi, Adi; Ubud, Sahnaz; Rekarti, Endi (Publikasi Indonesia, 2026)
Employee performance is a crucial factor in supporting the success of public sector organizations, including the Airport Operating Unit (UPBU), which plays a vital role in ensuring aviation safety, security, and service efficiency. Although the average performance achievement of the UPBU D.C. Saudale Office reached 97.01% based on the 2024 LAKIP report, significant challenges remain—particularly in the realization of Non-Tax State Revenue (PNBP), which fluctuated and achieved only 39.73% of the 2024 target. This gap indicates the need to examine factors influencing employee performance more comprehensively. This study applies a quantitative approach with an explanatory design to analyze the relationships among variables. The research involved 77 employees of the UPBU D.C. Saudale Office as respondents. The independent variables are competence and educational qualifications, the dependent variable is employee performance, and organizational commitment serves as a mediating variable. Data were analyzed using Structural Equation Modeling (SEM) to statistically test the proposed hypotheses. The findings reveal that competence and educational qualifications both have a positive and significant direct effect on employee performance. Competence also positively and significantly influences organizational commitment, while educational qualifications do not significantly affect organizational commitment. Organizational commitment has a positive and significant impact on employee performance and mediates the relationship between competence and performance; however, it does not mediate the relationship between educational qualifications and performance. Therefore, the organization should prioritize competency development programs, integrate education with practical training, and strengthen organizational commitment to enhance overall performance.